Penggunaan Kapasitor untuk Perbaikan Unjuk Kerja Motor Induksi sebagai Generator - Putra, I Ketut Perdana; Hadi, Sasongko Pramono; Haryono, T (Sekolah Pascasarjana UGM, 2004)
An induction motor can be operated as a generator by driving it above its synchronous speed. The advantages of induction motor used as generator in microhydro plants, comparised to synchronous generator is its low capital cost, low maintenance, easily operation, and readily available in the market in many size. The spesification data of induction motor used in this experiment is : 0,25 HP; voltage = 220/380 volt; I = 1,6 / 0,64 ampere; frequency = 50 Hz and nominal speed = 1500 rpm. The effect of capacitor compensation is known by changing the system parameters system values like power output, voltage drop, frequency and power factor. When the voltage drop is about 20% of nominal voltage and capacitor capacity is 14 F, the load is resistive load, the maximum output power is 67.160 watt. When the load is resistive-inductive, the output power is 44.756 watt, and when the load is inductive, the output power is 26.110 watt. The output power induction motor used as generator is about 42 % of its capacity when it is operated as a motor.